2015
DOI: 10.2139/ssrn.2676902
|View full text |Cite
|
Sign up to set email alerts
|

Maybe Next Month? Temperature Shocks, Climate Change, and Dynamic Adjustments in Birth Rates

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 49 publications
1
25
0
1
Order By: Relevance
“…For example, it has been shown that extreme heat reduces the number of children born exactly 9 months later but elevates births 11 to 13 months later, as some of the successful conceptions that would have occurred during the hot period, but did not, end up occurring in the near future (38). In these cases, where climatic events simply displace the timing of societal outcomes (a pattern illustrated in Fig.…”
Section: Using Research Design To Identify Causal Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it has been shown that extreme heat reduces the number of children born exactly 9 months later but elevates births 11 to 13 months later, as some of the successful conceptions that would have occurred during the hot period, but did not, end up occurring in the near future (38). In these cases, where climatic events simply displace the timing of societal outcomes (a pattern illustrated in Fig.…”
Section: Using Research Design To Identify Causal Effectsmentioning
confidence: 99%
“…(B) Tropical cyclones increase female infant deaths but with a delayed effect that grows rapidly roughly a year after exposure (49). (C) Birth rates in the United States fall 8 to 10 months after a hot day, but this decline is partially compensated for by an increase during months 11 to 13 (38). (D) GDP in countries exposed to tropical cyclones falls gradually but persistently during the 15 years following exposure (116 (48) and (B) effects of cyclones on GDP over time are most negative in countries with the lowest levels of historical experiencerank indicates quintile of exposure (116).Temperatureinduced mortality in the United States exhibits adaptation: (C) locations that have hotter long-run climates tend to have smaller effects (185) and (D) sensitivities have declined over time (43).…”
Section: Health Impacts: Early Lifementioning
confidence: 99%
See 1 more Smart Citation
“…This exploration is relevant because it could be the case that the negative economic effects of summer temperatures are diminished in the more recent part of the sample due to adaptation (for example, due to widespread adoption of air conditioning technologies as documented by Barreca et al (2015)). …”
Section: Stability Of the Effects Through Timementioning
confidence: 99%
“…This implies that the U.S. economy is still sensitive to temperature increases, despite the progressive adoption of adaptive technologies such as air conditioning (Barreca et al (2015)). We also document that the temperature effects are particularly strong in states with relatively higher summer temperatures, most of which are located in the South.…”
Section: Introductionmentioning
confidence: 99%